2009
DOI: 10.1016/j.jsv.2008.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation prediction of particle dampers

Abstract: This paper presents initial work on developing models for predicting particle dampers behaviour using the Discrete Element Method (DEM). In the DEM approach, individual particles are typically represented as elements with mass and rotational inertia. Contacts between particles and with walls are represented using springs, dampers and sliding friction interfaces. In order to use DEM to predict damper behaviour adequately, it is important to identify representative models of the contact conditions. It is particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(89 citation statements)
references
References 29 publications
2
79
0
2
Order By: Relevance
“…3. The friction coefficient μ = 0.3 for the friction between the particles and the coefficient of restitution of 95 % correspond well with the experimental values obtained by Wong et al [7].…”
Section: Dem Simulationsupporting
confidence: 89%
“…3. The friction coefficient μ = 0.3 for the friction between the particles and the coefficient of restitution of 95 % correspond well with the experimental values obtained by Wong et al [7].…”
Section: Dem Simulationsupporting
confidence: 89%
“…This has been demonstrated in a number of experiments and Molecular Dynamics (MD) simulations, including investigations on the attenuation of a free spring or cantilever with an attached granular damper [5,7,[22][23][24]. The response of an oscillating cantilever with respect to periodic forcing has also been studied [25][26][27][28][29][30]. Even more complex systems have been investigated, such as the oscillation modes of a plate with an abundance of granulate filled cavities [31][32][33][34] with the aim of noise reduction [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Energy dissipation of particle dampers was predicted by Wong et al [5] via the discrete element method. The results revealed that despite the fact that friction plays a leading role in energy dissipation, the actual friction coefficient has a little influence on energy consumption.…”
Section: The Combination Type Of Particle Dampersmentioning
confidence: 99%
“…[1,2] As the primary structure vibrates, kinetic energy is significantly absorbed through the combined effects of particle-to-particle and particle-to-wall inelastic collisions and frictional losses, producing considerable damping to the primary structure. [3][4][5][6] Particle damping technology has been widely Received: 23 February 2017 Revised: used due to its conceptual simplicity, moderate cost, good durability, and temperature insensitivity. Provided that the operating temperature is below the particles' metal melting point, it could maintain normal operation.…”
Section: Introductionmentioning
confidence: 99%